Biochemical characterization of the nucleic acids of some human and animal viruses - Mew, Ronald Terence (Division of Chemical Pathology, 2017)
In Part I, the isolation and partial characterization of human polyomaviruses from a number of renal transplant patients is described. These isolates proved refractory to cell culture propagation by the methods used, and were thus extracted directly from large volumes of patient's urine. This approach has the advantage that the virus cannot undergo any possible genomic modification, as tends to occur during adaptation to cell culture. Human polyomavirus DNA is very susceptible to mutation during cell passage. Four isolates from different patients yielded sufficient DNA for limited restriction endonuclease characterization. Surprisingly, all four gave the same patterns with EcoRI, BamHI and HindIII. Two isolates that were also digested with PstI gave an identical pattern. These patterns are similar to, but distinct from, other strains of the human polyomavirus BK that have been described. Our isolates had a similar-sized genome to BK, but only 3 HindIII sites compared with 4 in the prototype, and 2 PstI sites compared with only 1 in the prototype. The quantity of DNA obtained directly from urine was usually very limited. In order to produce adequate DNA for complete analysis, viral DNA was recombined with· a bacterial vector (pBR322) and cloned into Escherichia coli strains HB101 and C600. Initially, the well-studied strain BK(MM) was successfully cloned. This clone was used to prepare radioactively-labelled DNA probes for the detection of BK-specific sequences in urine isolates and in subsequent recombinants with patient material. Such cloned material is easier to prepare in bulk than DNA from virus passaged in cell culture. Early attempts to clone DNA from clinical isolates failed, but BK-specific DNA from a patient (P.R.) has recently been cloned successfully. These clones are presently being used to investigate the differences in sequence between our isolates and the known strains of BK. It is hoped that this will shed light on the mechanisms of gene expression of these potentially oncogenic viruses. In Part II, the genomes of four rotaviruses were studied. "Simian agent 11" (SAll) and "offal agent" (OA) were cell culture-adapted strains, whereas "epizootic diarrhoea of infant mice virus" (EDIM) and "infantile gastroenteritis virus" (IGV) were isolated from stool specimens. Experiments were performed to confirm the double-stranded RNA (dsRNA) nature of the SAll genome. It ran at a characteristic density of l.595g/ml in caesium sulphate density gradients, and was resistant to DNase and RNase at high ionic strengths, but susceptible to RNase at low ionic strength. At the start of the project few or no polyacrylamide gel pictures of the nucleic acids of these viruses had been published, although it was known they resembled reovirus in consisting of segmented double-stranded RNA. Such pictures were obtained, and molecular weight estimations made by comparison with dsRNA markers of known MW from a cytoplasmic polyhedrosis virus (CPV) from Heliothis armigera (Harley, Rubenstein, Losman and Lutton, 1977. Virology 76: 210-216). The difficulties in obtaining precise MW values for rotavirus genome segments are discussed. All four genomes consist of 11 dsRNA segments. The pattern of bands produced by PAGE is very similar, and high-resolution gels are required to detect the small mobility differences between some segments. Gel systems were developed to improve on the resolution obtained in co-electrophoresis experiments. During attempts to culture SAll and OA viruses in cell culture, it was observed that treatment of the cells and/or virus with versene-trypsin solution during infection gave a marked increase in virus yield. While this effect was being investigated, reports appeared on the potentiating effect of trypsin on the cell culture of previously refractory rotaviruses. We confirmed that trypsin, when present in the culture medium, greatly increased the yield of progeny SAll virus.